Association Between Non-hemolytic Anemia and Urinary Incontinence in Children Over 3 Years: A Case-control Study: Association Between Non-hemolytic Anemia and Urinary Incontinence - Adimi, Negin; Yousefichaijan, Parsa; Falahati, Vahid; Taherahmadi, Hassan; Sadjadei, Nooshin; Mobini, Arshia; Mohamadi Kamal, Amir Mahdi (Journal of Pediatric Nephrology, 2025)
Background and Aim: Urinary incontinence represents a significant pediatric health concern affecting children beyond the age of expected physiological control, with a substantial impact on quality of life. Anemia, particularly iron deficiency, is a widespread global health issue affecting a large proportion of children worldwide. This study aimed to evaluate the association between non-hemolytic anemia and urinary incontinence in children over three years of age. Methods: This case-control study included 260 children aged 3-16 years, divided into two equal groups: 130 children with non-hemolytic anemia (hemoglobin <11 g/dL) and 130 ageand sex-matched healthy controls. Participants were assessed for various types of urinary incontinence through structured interviews with parents using standardized questionnaires. Statistical analysis included the chi-square test, descriptive statistics, and logistic regression analysis to calculate odds ratios. Results: While general urinary incontinence showed no significant association with anemia (OR: 1.32; 95% CI, 0.81-2.16), monosymptomatic enuresis was significantly more prevalent in the anemic group (30.8% vs. 6.2%, P<0.001), with an odds ratio of 6.77 (95% CI, 3.02- 15.18). Conversely, underactive bladder was less common in anemic children (10.0% vs. 19.2%, P=0.035, OR: 0.46, 95% CI, 0.22-0.95). Among anemic children with urinary disorders, iron deficiency was the most common type, present in 49.4% of cases with urinary incontinence and 52.5% of cases with monosymptomatic enuresis. Conclusion: This study provides evidence for a significant association between nonhemolytic anemia and monosymptomatic enuresis in children over three years of age. Anemia screening should be considered in children presenting with monosymptomatic enuresis, particularly in regions with high rates of iron deficiency. Future research should explore the mechanisms behind these associations and assess whether treating anemia can improve enuresis symptoms.